Magnetic Property Analysis ZnFe2O4 Magnetic Nanomaterial Derived From Iron Sand Using the Coprecipitation Magnetic Method - Indah Nurpriyanti; Elisa Sulistyorini; Mastuki Mastuki (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
Iron sand is a natural resource rich in iron oxide compounds such as Fe₃O₄, α-Fe₂O₃, and γ-Fe₂O₃, which have the potential to be developed into functional materials, particularly magnetic nanoparticles. This study aims to analyze the magnetic properties of ZnFe₂O₄ nanomaterials synthesized from iron sand using the coprecipitation method. The synthesis was carried out by dissolving iron sand in HCl, mixing with a ZnCl₂ solution and titrating with NH₄OH until a dark brown precipitate was formed. The precipitate was heated at 200 °C for 2 hours. Characterization was conducted using X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Vibrating Sample Magnetometry (VSM). XRD results confirmed the presence of ZnFe₂O₄ phase by JCPDS No. 22-1012, with a crystallite size of 24.9 nm and a lattice parameter of 8.28 Å. SEM images revealed non-uniform particle morphology and agglomeration. VSM results showed a remanent magnetization (Mr) of 0.0016 emu, coercivity (Hc) of 314 Oe, and saturation magnetization (Ms) of 1.540 emu. Based on these results, the material exhibits soft ferromagnetic behavior consistent with the spinel structure of ZnFe₂O₄.